Anti-müllerian hormone and insulin-like 3 levels in healthy normal-weight ovulatory and anovulatory eumenorrheic late adolescent females: potential early biomarkers of ovarian dysfunction?. (December 2015) - Pelusi, Carla; Stancampiano, Marianna; Fanelli, Flaminia; Pariali, Milena; Gambineri, Alessandra; Pasquali, Renato
Abstract: Objective: The aim of this study was to evaluate differences in anti-müllerian hormone (AMH) and insulin-like 3 (INSL3) levels and their association with gonadotropin and ovarian steroid hormones, as expression of ovarian function, between healthy normal-weight ovulatory and anovulatory eumenorrheic late adolescent females. Study design: This study analyzed AMH and INSL3 levels in forty healthy eumenorrheic late adolescent females (aged 16–19 ys), selected from a cross-sectional epidemiological study performed on the prevalence of hyperandrogenic states. The subjects were divided into ovulatory ( n : 28) and anovulatory ( n : 12) groups in accordance to a previous cluster analysis based on progesterone (P) distribution measured once in the latter part of the cycle. Both groups were compared for anthropometric, biochemical and hormonal parameters. Results: INSL3 and AMH were detectable in all samples. Testosterone ( P  = 0.01), the free-androgen index (FAI) ( P  = 0.051), gonadotropins (LH: P  = 0.02; FSH: P  = 0.004) and AMH ( P  = 0.02) levels were significantly higher in the anovulatory group with respect to their ovulatory counterpart. A trend toward significantly higher INSL3 concentrations ( P  = 0.08) was also shown in the anovulatory group. A positive correlation between INSL3 levels and androgens such as androstenedione ( r  = 0.38; P  = 0.02), testosterone ( r  = 0.44; P  = 0.004) and FAI ( r  = 0.42; P  = 0.006) and a negative borderline significant correlation ( r  = −0.30; P  = 0.055) between AMH and P were shown in all subjects. Conclusion: Healthy eumenorrheic late adolescent females with sporadic anovulation display higher AMH and INSL-3 blood concentrations in association with higher androgen levels compared with age- and BMI-matched subjects with ovulatory cycle, suggesting evidence of an earlier ovarian dysfunction.